Evidence for increased background neural noise in migraine with aura: Hyperactive but not hyperresponsive. - O'Hare, Louise; Hibbard, Paul B.; Wilkins, Arnold J. (Headache: The Journal of Head & Face Pain, 2026)
Objective: This study had two aims: (1) to investigate the contrast gain in migraine and compare it to that in photosensitive epilepsy; (2) to explore any effects of colored spectacles (precision ophthalmic tints [POT]) on contrast gain. Background: Individuals with migraine with aura (MA) typically show high amplitude electrophysiological responses, but poor performance on visual tasks. One possible explanation is increased neural "noise" in the visual cortex in MA. "Noise" is neural activity that does not carry information about the stimulus. Methods: This is a case–control study of individuals with MA and controls with no family history of migraine, as there is a tendency for migraine to run in families. We measured the steady‐state visual evoked potential in response to a sinewave grating (striped pattern) that varied in contrast (appeared to flicker on and off) at 5 and 17 Hz in 15 MA and 15 control participants. The maximum contrast (stimulus intensity) increased progressively from 10% to 90% in nine equal steps. We also measured the effect of colored spectacles (POTs) on the electroencephalogram (EEG) response. The experiment was a mixed factorial design, with one between‐participants factor (experimental vs. control group) and two within‐participants factors (contrast and lens type [none, POT, or control]). The dependent variables were the steady‐state visual evoked potential response, and the background EEG activity. In experiment 2, discomfort judgments on a rating scale of 0–9 from a separate set of 12 MA and 12 control participants were also collected during the EEG session. Data were collected between February 2022 and August 2024. Results: At the faster flicker rate of 17 Hz (appearing on and off 17 times per second), the electrophysiological response of the MA group showed increased background activity (EEG power at frequencies other than the stimulation frequency) (experiment 1: mean for the migraine group = −666.45 dB/Hz, standard error [SE] = 116.69; mean for the control group = −1100.50 dB/Hz, SE = 164.99; coefficient estimate = 434.09, p = 0.016, confidence interval [CI], 82.24–735.94; estimated Cohen's d of 0.94, CI, 0.14–1.73; experiment 2: migraine group mean = −500.01 dB/Hz, SE = 122.99; control group mean = −741.88 dB/Hz, SE = 126.12; coefficient estimate = 265.04, p = 0.049, CI, 1.52–528.56, estimated Cohen's d of 0.95, CI, 0.05–1.84). The increase in EEG power with contrast at the stimulation frequency was similar in both MA and control groups. The MA group experienced more discomfort compared to the control group (median rating for migraine group = 4, interquartile range [IQR] = 4, median rating for control group = 3, IQR = 3, coefficient estimate = 3.58, p = 0.003, CI, 1.18–6.00) and faster flicker (17 Hz) was judged more uncomfortable than slower flicker (5 Hz) by both groups (median rating for 5 Hz = 3, IQR = 3, median rating for 17 Hz = 4, IQR = 4, coefficient estimate = 0.97, p < 0.001, CI, 0.49–1.45). There was no specific reduction in EEG response in the MA group compared to controls with POTs. Conclusions: The increased EEG responses in MA show evidence that in migraine the brain is "noisier" compared to controls. As the contrast response was similar in both MA and control groups, this suggests typical contrast gain control, as distinct from the abnormality seen previously in photosensitive epilepsy. The chosen color of POTs can reduce discomfort judgments under some circumstances, although this does not appear to be specific to MA. Plain Language Summary: People with migraine with aura (MA) and people with photosensitive epilepsy have similarities in terms of their sensitivities to visual stimuli. In this study, we used electrophysiological (EEG) recordings of brain activity in people with MA to determine if low‐level visual processing is similar to that in people with photosensitive epilepsy. We found evidence for different mechanisms of visual sensitivity in MA compared to photosensitive epilepsy, and there was consistent evidence of increased background brain activity in MA compared to people without migraine, suggesting greater neural "noise" in people who have MA.